2016
DOI: 10.1021/acs.iecr.5b04502
|View full text |Cite
|
Sign up to set email alerts
|

Synergy in the Cracking of a Blend of Bio-oil and Vacuum Gasoil under Fluid Catalytic Cracking Conditions

Abstract: The catalytic cracking of a blend of raw bio-oil (20 wt %) from black poplar sawdust fast pyrolysis and vacuum gasoil (VGO, 80 wt %) has been studied. The runs have been performed in a riser simulator reactor (RSR) under fluid catalytic cracking (FCC) conditions; that is, 500–560 °C, catalyst to feed mass ratio of 6 gcat (gfeed) –1 on a dry basis, reaction times of 3–10 s and a equilibrated commercial FCC catalyst. The cofeeding effect has been quantified by comparing the yields of product lumps and individual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 75 publications
(54 citation statements)
references
References 47 publications
2
52
0
Order By: Relevance
“…The oxygenate pathway, forming polyphenols residues with more aliphatic and oxygenated nature [41,42]from aldol condensation [43] and the hydrocarbon pathway, forming polycondensed aromatic structures. It is surprising that applying a temperature close to real FCC the test favours the hydrocarbons pathways in the coke composition even with of high content of oxygenates in the feed [37,44].…”
Section: Catalyst Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…The oxygenate pathway, forming polyphenols residues with more aliphatic and oxygenated nature [41,42]from aldol condensation [43] and the hydrocarbon pathway, forming polycondensed aromatic structures. It is surprising that applying a temperature close to real FCC the test favours the hydrocarbons pathways in the coke composition even with of high content of oxygenates in the feed [37,44].…”
Section: Catalyst Characterizationmentioning
confidence: 99%
“…Indeed, many studies have shown that the co-feeding strategy of oxygenates such as phenol [34,35], m-cresol [36] and bio-oil [37]with hydrocarbons increases the coke yield, which is ascribable to the strong adsorption of oxygenated molecules on zeolite acid sites. The FCC units are designed to handle coke on the catalyst to a certain extent.…”
Section: Catalyst Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…The synergies in the co‐processing of raw bio‐oil (20 wt%) and VGO were also studied by Ibarra et al . over a commercial FCC equilibrium catalyst at 500–560°C in a CREC riser simulator.…”
Section: Bio‐oil Upgrading To Fuels and Platform Chemicals By Catalytmentioning
confidence: 99%
“…Concerning oxygenated bio-derived streams (iii), a great research interest towards exploring the possibilities of bio-derived feedstock (i.e. bio-oil, vegetable oils) for FCC conversion has been studied [24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%